A review of level-1 visual perspective-taking: potential relationship with the uncanny valley effect - Fan, Cong; He, Weiqi (Frontiers in Psychology, 2024)
Calculating others' visual perspective automatically is a pivotal ability in human social communications. In the dot-perspective task, the ability is shown as a consistency effect: adults respond more slowly to judge the number of discs that they can see when a computer-generated avatar sees fewer discs. The implicit mentalizing account attributes the effect to relatively automatic tracking of others' visual perspective. However, the submentalizing account attributes the effect to domain-general attentional orienting. Accordingly, the current study focuses on elucidating the ongoing implicit mentalizing vs. submentalizing debate. The review tried to shed light on the debate regarding level-1 visual perspective taking and its potential relationship between the uncanny valley effect. Future research may focus on new manipulations of uncanny valley effect to further uncover the relationship between uncanny valley effect and level-1 visual perspective taking. This may provide new insight into the debate and the processing mechanisms of level-1 visual perspective-taking and uncanny valley effect, which may be beneficial for AI development.